Pengaruh Model Discovery Learning Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar (MI/SD) - Nafia Wafiqni; Alfina Nurul Huda; Edwita Edwita; Zulela M S; Gusti Yarmi (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
The ability to think at a high level in the 21st century is certainly very important, especially in the world of education which is expected to be able to produce a superior generation who is ready to face problems in the future. According to the Ministry of Education and Culture (2021) that Higher Education personnel and Indonesian students who are part of the productive age need to prepare themselves early by honing and improving 5C skills. This is in line with the construction of 5C skills consisting of Complex Problem Solving, Critical Thinking, Creativity, Coordinating with Others, Cognitive Flexibility. Critical thinking skills can be developed through a learning model, one of which is a discovery-based learning model (discovery learning). This study aims to determine the influence of the discovery learning model on the critical thinking ability of elementary school (MI / SD) students. This research uses a quantitative approach with quasi-experimental research methods with a nonequivalent control group design design. This study sampled 48 students. The data collection technique uses a question instrument in the form of a description consisting of 10 valid and reliable questions. Data analysis techniques for normality tests use kolmogorov-smirnov technique, for homogeneity tests using levene tests with test criteria based on mean and t-tests for hypothesis testing. To find out whether or not there is an influence on students' critical thinking skills, a t test is carried out using an independent sample t test. From the test results of the pretest hypothesis count = 0.882 and ttabel = 1.67, it can be concluded that there is no difference between the pretest results of the experimental class and the pretest results of the control class. As for testing the posttest hypothesis, the calculated value = 6.455 and ttabel = 1.67 were obtained, so it can be concluded that there is a difference between the posttest results of the experimental class and the posttest results of the control class. This can be interpreted to mean that the ability to think critically using the discovery learning model is higher than the conventional model (cooperative model).